Theoretically Guided Analytical Method Development and Validation for the Estimation of Rifampicin in a Mixture of Isoniazid and Pyrazinamide by UV Spectrophotometer - Khan, Mohammad F.; Rita, Shamima A.; Kayser, Md. Shahidulla; Islam, Md. Shariful; Asad, Sharmeen; Bin Rashid, Ridwan; Bari, Md. Abdul; Rahman, Muhammed M.; Al Aman, D. A. Anwar; Setu, Nurul I.; Banoo, Rebecca; Rashid, Mohammad A. (Frontiers in Chemistry, 2017)
A simple, rapid, economic, accurate and precise method for the estimation of rifampicin in a mixture of isoniazid and pyrazinamide by UV spectrophotometeric technique (guided by the theoretical investigation of physicochemical properties) was developed and validated. Theoretical investigations revealed that isoniazid and pyrazinamide both were freely soluble in water and slightly soluble in ethyl acetate whereas rifampicin was practically insoluble in water but freely soluble in ethyl acetate. This indicates that ethyl acetate is an effective solvent for the extraction of rifampicin from a water mixture of isoniazid and pyrazinamide. Computational study indicated that pH range of 6.0-8.0 would favor the extraction of rifampicin. Rifampicin is separated from isoniazid and pyrazinamide at pH 7.4 ± 0.1 by extracting with ethyl acetate. The ethyl acetate was then analyzed at λmax of 344.0 nm. The developed method was validated for linearity, accuracy and precision according to ICH guidelines. The proposed method exhibited good linearity over the concentration range of 2.5 - 35.0 µg/mL. The intraday and inter-day precision in terms of % RSD ranged from 1.09 - 1.70% and 1.63 - 2.99%, respectively. The accuracy (in terms of recovery) of the method varied from of 96.7 ± 0.9 to 101.1 ± 0.4%. The LOD and LOQ were found to be 0.83 and 2.52 µg/mL, respectively. In addition, the developed method was successfully applied to assay rifampicin combination (isoniazid and pyrazinamide) brands available in Bangladesh.